Effect of dosing schemes of amoxicillin on eradication rates of Helicobacter pylori with amoxicillin‐based triple therapy. (22nd October 2013) - Furuta, Takahisa; Sugimoto, Mitsushige; Yamade, Mihoko; Uotani, Takahiro; Sahara, Shu; Ichikawa, Hitomi; Yamada, Takanori; Osawa, Satoshi; Sugimoto, Ken; Watanabe, Hiroshi; Umemura, Kazuo
Abstract Objectives In standard regimens for Helicobacter pylori infection, amoxicillin is dosed twice daily, although the bactericidal effect of amoxicillin depends on the %time‐above‐MIC. We aimed to examine whether dosing schemes of amoxicillin influenced eradication rates of amoxicillin‐based regimens. Methods One hundred eighty‐seven patients infected with clarithromycin‐sensitive strains of H. pylori were treated with PPI, clarithromycin 200 mg bid and amoxicillin 750 mg bid, 500 mg tid or 500 mg qid for 1 week and 125 infected with clarithromycin‐resistant strains were treated with PPI, metronidazole 250 mg bid and amoxicillin 750 mg bid, 500 mg tid or 500 mg qid for 1 week. Results Eradication rates (ITT) of the triple PPI/amoxicillin/clarithromycin therapy with bid, tid and qid dosings of amoxicillin were 77.8% (49/63), 93.5% (58/62), and 91.9% (57/62), respectively. Those of the triple PPI/amoxicillin/metronidazole therapy were 80.5% (33/41), 90.5% (38/42), and 95.2% (40/42), respectively. Eradication rates in regimens with tid and qid dosing of amoxicillin were higher than those of regimens with the bid dosing of amoxicillin. Conclusions The dosing scheme of amoxicillin significantly influenced eradication rates of triple therapies. Although amoxicillin is empirically dosed twice daily, amoxicillin should be dosed at least three times daily in amoxicillin‐based triple therapies.